Effective multiple stages continuous acetone–butanol–ethanol fermentation by immobilized bioreactors: Making full use of fresh corn stalk. (April 2016) - Chang, Zhen; Cai, Di; Wang, Yong; Chen, Changjing; Fu, Chaohui; Wang, Guoqing; Qin, Peiyong; Wang, Zheng; Tan, Tianwei
Highlights: Three-stage immobilized fermentation process was established for ABE production. 18–22 g/L of ABE solvents with 0.61–0.92 g/L h of productivity was achieved using corn stalk juice as substrate. The process showed good performances in ∼400 h of operation. Abstract: In order to make full use of the fresh corn stalk, the sugar containing juice was used as the sole substrate for acetone–butanol–ethanol production without any nutrients supplement, and the bagasse after squeezing the juice was used as the immobilized carrier. A total 21.34 g/L of ABE was produced in batch cells immobilization system with ABE yield of 0.35 g/g. A continuous fermentation containing three stages with immobilized cells was conducted and the effect of dilution rate on fermentation was investigated. As a result, the productivity and ABE solvents concentration reached 0.80 g/L h and 19.93 g/L, respectively, when the dilution rate in each stage was 0.12/h (corresponding to a dilution rate of 0.04/h in the whole system). And the long-term operation indicated the continuous multiple stages ABE fermentation process had good stability and showed the great potential in future industrial applications.